1999
DOI: 10.21900/j.inhs.v36.123
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Ingested Zinc Shot to Game-farm Mallards

Abstract: We conducted a 30-day acute toxicity test of zinc (Zn) shot using 6- to 8-month-old wild-type game-farm Mallards (Anas platyrhynchos), 40 of which (20 males and 20 females) were dosed with 6 No. 4 candidate shot pellets containing 98% Zn and 2% tin (Sn); the remaining 40 ducks were dosed with 6 No. 4 steel (Fe) shot and served as controls. The Zn shot resulted in high mortality, with a greater proportion of females dying than males. For the 30-day study, survival averaged 18 and 23 days for female and male Zn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…Arsenic levels in our study (Table 2) were below the mean levels of 3–6 µg g −1 found in four owl species in Spain (Perez-Lopez et al 2008) and far below a suggested deleterious level of 56 µg g −1 measured in a dead North American osprey (Wiemeyer et al 1980). Zinc levels in the four owl species in Spain (Perez-Lopez et al 2008) averaged 2–3 times higher than in this study, but the highest concentrations in our sample (Table 2) were within the lower ends of ranges for levels associated with deleterious effects in waterfowl (Doneley 1992; Levengood et al 1999; Sileo et al 2003). For other trace metals studied here, there is not much published information about critical thresholds for concentrations in bird liver.…”
Section: Discussioncontrasting
confidence: 51%
“…Arsenic levels in our study (Table 2) were below the mean levels of 3–6 µg g −1 found in four owl species in Spain (Perez-Lopez et al 2008) and far below a suggested deleterious level of 56 µg g −1 measured in a dead North American osprey (Wiemeyer et al 1980). Zinc levels in the four owl species in Spain (Perez-Lopez et al 2008) averaged 2–3 times higher than in this study, but the highest concentrations in our sample (Table 2) were within the lower ends of ranges for levels associated with deleterious effects in waterfowl (Doneley 1992; Levengood et al 1999; Sileo et al 2003). For other trace metals studied here, there is not much published information about critical thresholds for concentrations in bird liver.…”
Section: Discussioncontrasting
confidence: 51%
“…The geometric mean of hepatic Cu in the livers of common pochard Aythya ferina was 101.4 mg/kg ww (405.6 mg/kg dw) then, while for the red-crested pochard Netta rufina it was 134.51 mg/kg ww (538.04 mg/kg dw) (Taggart et al, 2006). In mallards, signs of Zn poisoning were not discerned until the hepatic concentrations were between 473 and 1990 mg/kg dw (Levengood et al 1999) or 280 and 2900 mg/kg dw (Sileo et al, 2003). On the other hand, Carpenter et al (2004) discovered that in trumpeter swan Cygnus buccinator, symptoms of Zn poisoning were associated with mining wastes and resulted in Zn liver concentrations of 154 mg/ kg ww (616 mg/kg dw).…”
Section: Discussionmentioning
confidence: 98%
“…It is known that some of the other metals (cobalt, copper, nickel, tungsten, zinc) that can be used as an alternative for lead in ammunition are characterized by biotoxicity (Grandy et al, 1968;Levengood, 1999;Bardack et al, 2014;Paulsen and Sager, 2017;Thomas, 2016Thomas, , 2019.…”
Section: Introductionmentioning
confidence: 99%